Characterization of minor pilins in Pseudomonas aeruginosa - Giltner, Carmen (My University, 2010)
Type II Secretion (T2S) and type IV pilus (T4P) systems in Gram-negative bacteria share many features that suggest a common ancestral origin. This study examined the role of the minor pilins FimU, PilV, PilW, PilX and PilE, as well as the putative adhesin PilYl in both the T4P and T2S systems, and elucidated the role of these proteins in pilus assembly. Genetic analysis of the major pilin cluster and the minor pilin operon revealed that the major pilin alleles are associated with a specific set of minor pilins, and that unrelated strains of the same major pilin type have identical minor pilin genes, suggesting that the two gene clusters were horizontally acquired as a 'pilin island'. We observed that the minor pilins required a specific stoichiometric ratio for proper assembly, as overexpression either completely abolished, or significantly reduced twitching motility in mutant backgrounds. We demonstrated that the minor pilins were incorporated into the pilus fibre, and that they were dependent on PilA for surface localization. The T4P minor pilins were also shown to play a role in the secretion of effectors through the T2S system, as elastase and haemolytic phospholipase C secretion was reduced in minor pilin mutants, while overexpression of FimU or PilX significantly increased secretion of T2S exoproteins. Therefore, the minor pilins may participate in T2S substrate recognition. We found that PilYl was not essential for assembly in the absence of retraction, but that its absence caused changes in the levels of other T4P biogenesis proteins, namely FimU, PilW, PilF and PilQ secretin multimers. Finally we show that the minor pilin, PilX functions as a strain-specific factor, potentially through specific interactions with non-conserved residues of PilQ that are necessary to induce opening of the secretin.
Keywords: minor pilins; Pseudomonas aeruginosa; Gram-negative bacteria; putative adhesin